Integrating Pega's AI-Driven Workflows for End-to-End Process Optimization in Financial Services - Kartheek Kalluri (North American Journal of Engineering Research, 2024)
In fast-growing financial services, operation, cost containment, and compliance are critical success factors. Leveraging Pega is best for integrating its AI-based workflows which encompasses end-to-end process handling and decision-making. This paper aims at establishing how Pega Systems is using artificial intelligence in the execution of intricate financial processes to achieve accuracy, reproduce-ability and satisfaction among its clients. Some of the technologies that imbue Pega include RPA, NLP, andpredictive analysis to support integration with traditional systems and improve the premium operations of credit loan granting, credit fraud detection, and compliance monitoring Primarily, case-driven and numerical data analysis in this article reveals the following key findings of the direct impact of the solution’s implementation: Overall, the advantages of the solution can be summarized by the following findings of the study: Issues associated with the integration of GPT with LLMs as well as some ethical issues in the next AI decision-making process are also discussed, as well as the future developments such as generative AI and broader application of AI in digital banking and ESG reporting. This paper provides guidance to financial organizations planning on implementing Pega’s AI solutions as astrategy in the growing automated market.